The Uniqueness of the Early Childhood profession a discussion with M. Almy [videorecording]. - Almy, Millie Corinne; National Association for the Education of Young Children ([South Carolina] South Carolina Educational Television Network, 1985)
Describes how early childhood education differs from other levels of education and the preparation and skills required to teach young children.
Executive producer for NAEYC, Dr. J.D. Andrews ; Executive producer for SCETV, Carolyn S. Dorrell.
Keywords: Education, Preschool -- Teacher training